Qualitative Research Protocols for Measuring Gendered Constraints to Employment and Entrepreneurship in Malawi - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The qualitative research protocols were designed by the International Food Policy Research Institute (IFPRI) in collaboration with the Millennium Challenge Corporation (MCC) to identify issues that most constrain women’s access to employment and entrepreneurship opportunities in Malawi and to understand how benefit streams for economic growth due to low participation of women in employment and entrepreneurship can be unlocked through removing constraints. More broadly, the protocols are part of an effort to improve the integration of gender into growth constraints diagnostics, an analytic approach commonly used by development organizations, such as MCC, to identify ‘binding’ constraints to economic growth within a particular economy and prioritize policy reforms to ease those constraints.